Influence of Competence, Independence, Tenure Audit and Quality of Financial Reports on Audit Quality - Tata Tata Angraini; Yuhanis Ladewi; Aprianto Aprianto; Ida Zuraidah; Helliana Helliana (Kajian Akuntansi, 2023)
Objective study This For know influence auditor competence to audit quality, influence auditor independence against audit quality, tenure audit influence on audit quality and influence quality report finance to audit quality. Type study is associative and descriptive. Place study done in the accounting office Public in Palembang City. Variables used is auditor competence, auditor independence, audit tenure, quality report financial and audit quality. Data used are primary and secondary. Method data collection used is questionnaires and interviews. Deep data testing study This is the validity test and reliability test. Data analysis technique used is statistics descriptive and statistical inferential helped with Statistical Program For Special Science (SPSS). Research results show that influential auditor competence to audit quality, auditor independence effect to audit quality, influential tenure audit to audit quality and quality report finance influential to audit quality.